Quality of Patient Care at a Health Center in Ecuador, 2024 - Bravo , Mgtr. Lissette Gabriela Beltrán; Rodríguez, Mgtr. María Emilia Ojediz; Mite, Mgtr. Ana Ivonne Alarcón; Loor, Mgtr. Jeniffer Lucía Mora; Torres, Mgtr. Daniel Joel Petroche (Journal of Ecohumanism, 2024)
The study entitled, Quality of Patient Care at the Health Center of a Canton in Ecuador, 2024, aimed to identify and propose strategies to optimize the quality of care at the health center. The research used a descriptive quantitative methodology, with surveys of patients and health personnel to evaluate factors such as infrastructure, staff treatment and waiting time. Among the main results, it was observed that user satisfaction is highly influenced by staff training, availability of medicines and appointment management. In addition, it was determined that infrastructure and the use of technology significantly improve the perception of service quality. In conclusion, the study recommends a comprehensive strategy that includes continuous staff training, adequate infrastructure, an efficient appointment system and a reliable supply of medical supplies. These elements are essential to increase patient satisfaction and efficiency in health center care.